CREATING VALUE THROUGH MANAGING CORPORATE RISK: INSURANCE, FINANCIAL PRODUCTS AND FINANCIAL STRATEGIES - Doherty, Neil A. (Assurances)

(untitled) (HEC Montréal, 2000)
Corporate risk management has evolved in several ways over the past two decades. It has evolved from addressing insurance risk to financial and other business risks, it has expanded to embrace a wide variety of hedging products and integrated strategies are now often adopted. Another less conspicuous, though probably more important, development has been the recognition that risk management and corporate finance strategies can address the same problems. The choice of leverage, contingent leverage, postloss financing, contingent equity, limited liability and similar approaches can substitute or complement more traditional risk management strategies. Here the author will present results of recent literature on why risk is costly to firms and outline both the hedging and corporate finance strategies for addressing these various costs.